2002
DOI: 10.1124/mol.62.6.1464
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Agonists Differentially Regulate μ-Opioid Receptors and Trafficking Proteins in Vivo

Abstract: Chronic opioid agonist treatment produces tolerance and in some cases opioid receptor internalization and down-regulation. Both morphine and etorphine induce tolerance; however, only etorphine produces -opioid receptor (OR) down-regulation. In vitro studies implicate dynamin-2 (DYN-2) and Gprotein receptor kinase-2 (GRK-2) in these processes. Therefore, we examined etorphine and morphine effects on regulation of GRK-2 and DYN-2 in mouse spinal cord. Mice were treated for 7 days with etorphine (200 g/kg/day inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…It is widely speculated that differences in short-term MOR regulatory events underlie the profound agonist-selective differences observed in the development of tolerance in vivo (Whistler et al, 1999;Stafford et al, 2001;Walker and Young, 2001;Patel et al, 2002;Grecksch et al, 2006;Pawar et al, 2007). There is no consensus, however, on which elements of MOR regulation-signaling efficacy, desensitization, internalization, or resensitization-are most directly correlated with tolerance (Whistler et al, 1999;Bohn et al, 2000;Williams et al, 2001;Connor et al, 2004;von Zastrow, 2004;Bailey and Connor, 2005;Koch et al, 2005).…”
Section: Enkephalin (Me) [D-alamentioning
confidence: 99%
“…It is widely speculated that differences in short-term MOR regulatory events underlie the profound agonist-selective differences observed in the development of tolerance in vivo (Whistler et al, 1999;Stafford et al, 2001;Walker and Young, 2001;Patel et al, 2002;Grecksch et al, 2006;Pawar et al, 2007). There is no consensus, however, on which elements of MOR regulation-signaling efficacy, desensitization, internalization, or resensitization-are most directly correlated with tolerance (Whistler et al, 1999;Bohn et al, 2000;Williams et al, 2001;Connor et al, 2004;von Zastrow, 2004;Bailey and Connor, 2005;Koch et al, 2005).…”
Section: Enkephalin (Me) [D-alamentioning
confidence: 99%
“…It seemed likely that antagonist efficacy might determine up-regulation and supersensitivity given that previous studies indicate that agonist efficacy plays a role in -opioid receptor down-regulation and tolerance (e.g., Pawar et al, 2007). Although data indicate that antagonistinduced up-regulation and agonist-induced down-regulation are mechanistically distinct (e.g., Yoburn et al, 2004;Pawar et al, 2007), the evidence linking agonist efficacy, tolerance, and receptor regulation is compelling (Patel et al, 2002;Pawar et al, 2007), and some studies have suggested that antagonist efficacy may be important in up-regulation and supersensitivity (Morris and Millan, 1991;Milligan and Bond, 1997). Therefore, it seemed plausible that antagonist efficacy might have an impact on -opioid receptor up-regulation and functional supersensitivity.…”
mentioning
confidence: 96%
“…Receptor density regulation is a well documented phenomenon in the opioid system (e.g., Yoburn et al, 1986;Keith et al, 1996Keith et al, , 1998Patel et al, 2002). Both opioid agonists and antagonists have been shown to regulate -opioid receptor density (Chakrabarti et al, 1997;Zaki et al, 2000;Rajashekara et al, 2003), and these changes can have an impact on the potency of opioid agonists (e.g., Stafford et al, 2001;Patel et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation and trafficking of -opioid receptors has been shown to be agonist-dependent (Sternini et al, 1996;Whistler and von Zastrow, 1998;Alvarez et al, 2002;Patel et al, 2002;Borgland et al, 2003). Most agonists, when applied at saturating concentrations, cause receptor desensitization and internalization.…”
Section: Desensitization and Receptor Reservementioning
confidence: 99%